PENERAPAN APLIKASI SIPIO BERBASIS SMARTPHONE UNTUK MENINGKATKAN PELAYANAN FARMASI KLINIK APOTEKER DI RSUD SIMPANG LIMA GUMUL KEDIRI - Wiyati, Eni Rohma (Universitas Kadiri, 2023)
The world increasingly familiar with the digital world encourages the government to transform, especially in public services. Digital transformation in the public service sector is principally carried out to present public services that can adapt to society's needs. This will be optimal if it is carried out collaboratively across agencies regarding data utilization and service delivery. This collaboration is not limited to between government agencies but also across BUMN/D and private parties to provide excellent service to the community. For this reason, policies have been established that encourage and direct the four targets of accelerating the transformation of public services, namely the realization of electronic-based public services for each type of service (e-service), public complaints as the basis for public service policies, strengthening innovation ecosystems and strengthening integrated services. In supporting this, ASN, especially supervisory officials, need insight into technological developments in preparing organizations to utilize technology that suits their needs in improving electronic-based public services (e-services) to the public. The SIPIO application (Consultation and Drug Information Services) was created as an innovative service that can maximize the pharmacist's clinical pharmacy work so that patients or health workers who need information about drugs can easily communicate with pharmacists.